PENGARUH MOTIVASI KERJA DAN PENGEMBANGAN PEGAWAI TERHADAP PRESTASI KERJA PEGAWAI (Studi Pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Sumbawa) - Dela Anjelita; Arisa Dekayasa; Sri Rahayu (Pusat Riset dan Publikasi, 2022)
This study aims to determine the effect of work motivation and employee development on employee performance at the Department of Public Works and Spatial Planning in Sumbawa Regency, either partially or simultaneously. The type of this research is associative research. The type of data used is quantitative data obtained from primary sources in the form of respondents' responses in answering the questionnaire given. The source of the data in this study was determined using the cencus sampling technique, namely the entire population was used as the research sample so that the respondents in this study were all 34 employees of the Sumbawa Regency Public Works and Spatial Planning Service. Data analysis was performed using multiple linear regression analysis techniques, partial test (t test), simultaneous test (F test), and coefficient of determination test (R2). The results of this study indicate that work motivation and employee development have a positive and significant effect on employee work performance at the Sumbawa Regency Public Works and Spatial Planning Office, either partially or simultaneously. The effect of work motivation and employee development on employee performance at the Department of Public Works and Spatial Planning in Sumbawa Regency is 81.8%, while the remaining 18.2% is influenced by other variables outside this research model.